The impact of social grants as anti-poverty policy instruments in South Africa : an analysis using household theory to determine intra-household allocation of unearned income - Lekezwa, Bongisa Indira (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MComm)--University of Stellenbosch, 2011.